Impact of Hematopoietic Stem Cell Transplantation on PD-1 Blockade Efficacy in Relapsed/Refractory Hodgkin’s Lymphoma - Filomena Emanuela Laddaga; Pierluigi Masciopinto; Valentina Bozzoli; Domenico Pastore; Vincenzo Pavone; Angelo Michele Carella; Nicola Di Renzo; Attilio Guarini; Pellegrino Musto; Francesco Gaudio (Transplantology, 2025)
Background: Classical Hodgkin lymphoma (cHL) is a treatable malignancy; however, relapsed or refractory (R/R) cases pose significant challenges. PD-1 inhibitors have shown efficacy, but the role of hematopoietic stem cell transplantation (HSCT) following PD-1 blockade remains uncertain. This study aims to evaluate the impact of HSCT after PD-1 blockade on progression-free survival (PFS) and overall survival (OS) in patients with R/R cHL. Methods: We conducted a multicenter, retrospective study involving 42 patients with R/R cHL who received PD-1 inhibitors between 2016 and 2021. Patients were categorized into two groups: those who underwent HSCT after PD-1 therapy (n = 19) and those who continued PD-1 inhibitors without HSCT (n = 23). Results: Among the 42 patients, 27 achieved complete remission (CR) and 15 achieved partial remission (PR) following PD-1 blockade. In the HSCT group, 92% of patients remained progression-free at 3 years, compared to 65% in the non-HSCT group (p = 0.021). OS rates were similar between groups (100% vs. 96%, p = ns). Notably, 80% of PR patients in the HSCT group converted to CR. Relapse rates were significantly lower in the HSCT group (5%) compared to the non-HSCT group (43%, p = 0.005). Conclusions: HSCT following PD-1 blockade enhances PFS in patients with R/R cHL, particularly among those with PR, without offering a significant OS benefit. Further research is warranted to optimize treatment strategies for this patient population strategies.